2017
DOI: 10.1103/physreve.95.052120
|View full text |Cite
|
Sign up to set email alerts
|

Similarity law for Widom lines and coexistence lines

Abstract: The coexistence line of a fluid separates liquid and gaseous states at subcritical pressures, ending at the critical point. Only recently, it became clear that the supercritical state space can likewise be divided into regions with liquid-like and gas-like properties, separated by an extension to the coexistence line. This cross-over line is commonly referred to as the 2 * dbanuti@stanford.edu 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…For van der Waals Argon, c V is constant, therefore Widom anomaly does not exist for this quantity. Detailed description about the relation of Widom lines and coexistence lines of different species were given by Banuti et al [21].…”
Section: Methodsmentioning
confidence: 99%
“…For van der Waals Argon, c V is constant, therefore Widom anomaly does not exist for this quantity. Detailed description about the relation of Widom lines and coexistence lines of different species were given by Banuti et al [21].…”
Section: Methodsmentioning
confidence: 99%
“…G.G.Simeoni et al [8] carried out inelastic X-ray scattering and molecular dynamics simulation to find out a demarcation line between two dynamically different regime ("liquidlike" and "gaslike") in supercritical fluid around critical point called Widom line. In a recent study, however, it has been found that this Widom line doesn't obey the corresponding states principle and the transition lines differ with different fluids [9]. Few years back, the discovery of Frenkel line in the phase diagram further adds to the * kankaghosh@physics.iitm.ac.in.…”
Section: Introductionmentioning
confidence: 99%
“…As a reference line, we use the supercritical gas-liquid boundary (SGLB), defined as the loci of equal liquid and gas fractions, π gas = π liq = 0.5, in the supercritical domain (T > T c ). Taking the SGLB, which is also the line of maximal instability, as a reference is based on two observations: (i) near the LGCP, the Widom line and the SGLB closely coincide 16 , and (ii) the vapor-liquid equilibrium line (VLE), the LGCP, and the Widom line can be framed together within an extended corresponding states principle 20 . Therefore, we employ the postulate that the SGLB is the extension of the VLE and LGCP into the supercritical region 2/10 The phase diagram of the order parameter π gas , as computed by the machine learning classifiers ( Fig.…”
Section: Main Textmentioning
confidence: 99%